(untitled) (Higher Education Politics and Economics, 2025)
Institutional politics and emerging changes to the professoriate have potentially positioned tenure-track faculty within an academic labor system that assumes academic training and expertise guides their progression. This qualitative narrative study of 12 higher education and student affairs (HESA) pre-tenure faculty explored their navigation of tenure experiences at their institutions. Participants shared personal and professional challenges related to tenure in which they were challenged to negotiate academic and student affairs professional identities. Personal challenges included strained personal lives and relationships with feelings of isolation or loneliness. These findings offer insight into HESA pre-tenure faculty experiences as an avenue to better support this unique population. Study implications center equitable practices and community building.